2015
DOI: 10.1093/mnras/stv425
|View full text |Cite
|
Sign up to set email alerts
|

Probing model interstellar grain surfaces with small molecules

Abstract: Temperature-programmed desorption and reflection-absorption infrared spectroscopy have been used to explore the interaction of oxygen (O 2 ), nitrogen (N 2 ), carbon monoxide (CO) and water (H 2 O) with an amorphous silica film as a demonstration of the detailed characterization of the silicate surfaces that might be present in the interstellar medium. The simple diatomic adsorbates are found to wet the silica surface and exhibit first-order desorption kinetics in the regime up to monolayer coverage. Beyond th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
81
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(95 citation statements)
references
References 63 publications
(72 reference statements)
13
81
0
Order By: Relevance
“…The latter feature was left unidentified. It has been suggested that this unassigned feature could be CO in a CH 3 OH matrix, 51 but an assignment of CO directly adsorbed to the silicate surface 6 is also compatible with the results of the investigation and model suggested herein. On carbonaceous surfaces, the situation is less clear.…”
Section: Astrophysical Implicationssupporting
confidence: 88%
See 3 more Smart Citations
“…The latter feature was left unidentified. It has been suggested that this unassigned feature could be CO in a CH 3 OH matrix, 51 but an assignment of CO directly adsorbed to the silicate surface 6 is also compatible with the results of the investigation and model suggested herein. On carbonaceous surfaces, the situation is less clear.…”
Section: Astrophysical Implicationssupporting
confidence: 88%
“…As explained in the introduction, TPD experiments have shown that H 2 O clusters at all exposures on various surfaces. [6][7][8][9][10][11] A key consequence of these observations is that the established Onion Model of COM growth, i.e. a layered polar and apolar structure subject to energetic and thermal processing, should be revised.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The final results depend on the nature of the substrate from which the species desorbs. As an example, we would like to mention the reported experimental values of E bind for water, which may range from 4800 K, as reported by Dulieu et al (2013) from studies of formation of water on amorphous silicate surfaces, to 5930±240 K, as reported by Collings et al (2015), based on experiments of desorption from amorphous silica. Whether experiments are performed in the monolayer or multilayer regime and whether the deposited ice is pure, mixed, or layered also has an effect.…”
Section: Binding Energiesmentioning
confidence: 95%